Listeria monocytogenes infection in intestinal epithelial Caco-2 cells with exposure to progesterone and estradiol-17beta - Anna Marie Hugon; Thaddeus G. Golos (PLoS ONE, 2025)
Listeria monocytogenes (Lm) is a food-borne pathogen associated with serious pregnancy complications, including miscarriage, stillbirth, preterm birth, neonatal sepsis, and meningitis. Although Lm infection within the gastrointestinal tract is well studied, little is known about the influence sex hormones may have on listeriosis. Estradiol-17beta and progesterone not only have receptors within the gastrointestinal tract but are significantly increased during pregnancy. The presence of these hormones may play a role in susceptibility to listeriosis during pregnancy. Caco-2 cell monolayers were grown on trans-well inserts in the presence of estradiol 17-beta (E2), progesterone (P4), both hormones, or no hormones (control). Cells were inoculated with Lm for 1 hour, before rinsing with gentamycin and transfer to fresh media. Trans-epithelial resistance was recorded hourly, and bacterial burden of the apical media, intracellular lysates, and basal media were assessed at 6 hours post inoculation. There were no significant differences in bacterial replication when directly exposed to sex steroids, and Caco-2 cell epithelial barrier function was not impacted during culture with Lm. Addition of progesterone significantly reduced intracellular bacterial burden compared to estradiol 17-beta only and no hormone controls. Interestingly, estradiol 17-beta only treatment was associated with significantly increased Lm within the basal compartment, compared to reduction in the intracellular and apical layers. These data indicate that the sex hormones P4 and E2 alone do not significantly impact intestinal epithelial barrier integrity during listeriosis, but that addition of P4 and E2, alone or in combination, was associated with reduced epithelial cell bacterial burden and apical release of Lm.